Bilateral relations between the Republic of India and the Republic of Serbia - Maric , Vladimir (Napredak, 2021)
The text outlines and analyses the relations between India and Serbia from the formal establishment of diplomatic relations in 1948 till the present. The author gives special attention to the political and economic relations between the two countries. In the context of political relations, the author discusses the meetings that took place at the highest level as well as the significance of the Non-Aligned movement. With regard to economic relations, the paper points to the importance of bilateral cooperation that has developed since the establishment of diplomatic relations and has intensified in the past few years, with concrete results being achieved.